Studi Kelayakan Sabun Susu Sebagai Souvenir di Desa Wisata Menari, Kabupaten Semarang - Nasya Aisyah, Estrelita; Monik, Monik; Hendrawan, Fathur; Arlina, Ika Wahyu; Adi Mukti, Faizal (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
Menari Tourism Village in Semarang Regency is an area that is developing local potential through natural milk soap products as education-based souvenirs. This product is designed not only as a tourist souvenir, but also as a learning tool in cultural and creative tour packages. This study aims to assess the feasibility of a milk soap business as a flagship product of a tourist village through a feasibility study approach from market, technical, managerial, legal, environmental, and financial aspects. The method used is a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, participatory observation, and documentation. The results showed that milk soap has good prospects to be developed, supported by community involvement, availability of local raw materials, and effective digital marketing strategies. However, a number of challenges such as limited production capacity, technical skills, and not optimal business legality are still obstacles. Therefore, strengthening the institutional structure, training of human resources, preparation of SOPs, and sustainable promotion strategies are needed to ensure the sustainability and professionalism of the business in the future.